Quality evaluation of flat rice noodles (kway teow) prepared from bario and basmati rice - Rachel Thomas; T.K., Yeoh; Wan-Nadiah, W.A.; Rajeev Bhat (Universiti Kebangsaan Malaysia, 2014)
In the present study, rice noodles (kway teow or flat rice noodles) prepared from Bario rice, a locally grown, popular, organic rice variety of Malaysia was compared with rice noodles prepared from Basmati rice (imported from Pakistan). The quality criteria evaluated included determination of physical (colour and texture), cooking and sensory qualities. Additionally, microbial quality of fresh and stored noodles (stored for 3 days with 0 day as control) was also determined. The results showed tensile strength and elasticity modulus of rice noodles to decrease on storage with Basmati rice showing the lowest value for both the parameters analyzed (24.11 and 7.89 kPa, respectively). The cooking loss of rice noodles increased on storage in both rice varieties with Basmati rice showing higher range of 5.9-7.14%. With regard to colour, significant differences was observed between storage days for the parameters analyzed (L*, a* and b*). Overall, L* value of noodles prepared from Bario as well as Basmati rice showed a decrease on storage (became darker). With regard to microbial quality, aerobic plate count as well as yeast and mold counts increased significantly during storage. The results on sensory qualities showed colour (6.67), appearance (6.8) and texture (6.67) of fresh rice noodles to be significantly higher in Bario rice compared with Basmati rice. From the results, it was concluded that both Bario and Basmati rice can be explored effectively for preparing ‘kway teow’ or the flat rice noodles, which is envisaged to hold high promise in local market.